From bondage to freedom Spinoza on human excellence - LeBuffe, Michael (New York ; Oxford : Oxford University Press, 2010)
Building interconnected readings of Spinoza's accounts of imagination, error, and desire, Michael LeBuffe defends a comprehensive interpretation of Spinoza's enlightened vision of human excellence.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Spinoza, Benedictus de, -- 1632-1677.; Ethics; Philosophical anthropology